Exploring the value of organizational support, engagement, and psychological wellbeing in the volunteer context - Dekel, Grace; Geldenhuys, Madelyn; Harris, Jemma (Frontiers in Psychology, 2022)
In Australia, young adults are more likely to experience psychological distress than other age-groups. Accordingly, volunteer work engagement may act as an important tool for supporting psychological wellbeing. The present study relies on the job demands–resources model and self-determination theory to help understand the negative consequences of high work demands and the importance of effective organizational support to enhance positive mental health outcomes. To address research gaps, the current study explores these concepts for the young adulthood cohort in not-for-profit organizations. The study aims to explore the relationship between psychological wellbeing, volunteer work engagement, and perceived organizational support. The study used a quantitative, cross-lagged, longitudinal method for collecting data from two online surveys completed 4 weeks apart. The inclusion criteria of participants were volunteers who worked a minimum of 4 h a month (on average), resided in Australia, and were between 19 and 40 years old (N = 202). The main study findings were that perceived organizational support mediated the relationship between psychological wellbeing at time point 1 and volunteer engagement at time point 2. However, perceived organizational support did not mediate volunteer engagement at time point 1 and psychological wellbeing at time point 2. There were no bidirectional effects between volunteer engagement and psychological wellbeing. The findings contributed to the existing literature, suggesting there are overlaps between support mechanisms and motivation between paid and unpaid work. The practical implications for not-for-profit organizations are the importance of providing organizational support for young adult volunteers to improve wellbeing outcomes. Limitations and future study recommendations are presented.